For a Relational, Historical Ethnography of Hope: Indeterminacy and Determination in the Bosnian and Herzegovinian Meantime. Issue 4 (7th August 2016) - Jansen, Stef
ABSTRACT: This article aims to contribute to the formulation of an analytically operational notion of hope best suited to its treatment as an object of ethnographic investigation. First, it dissects epistemological and political assumptions of recent writings on the burgeoning anthropology of "hope". Then, reflecting on an ethnographic study of temporal reasonings in the "Meantime" in supervised, post-war, postsocialist, post-Yugoslav and presumably Europeanizing Bosnia and Herzegovina, it constructs a critical conversation between anthropological replications of hope that seek to valorize indeterminacy as a principle and studies in the political economy of hope that seek to understand determinations of hope (including people's engagements with indeterminacy) in particular conditions. The article argues that the latter approach—conceiving of hope as a relational phenomenon in historical time—is better placed to capitalize on the specific strengths of ethnographic research.